Assess the knowledge level of POZ patients on the diagnosis and treatment of type 2 diabetes - Żebrowska, Małgorzata; Medak, Edyta; Pachuta, Małgorzata; Brodowicz-Król, Magdalena (Journal of Education, Health and Sport, 2017)
Background: Diabetes is considered a civilization disease. It is now one of the major problems of the modern world. More than 123 million people suffer from it. About 3.5% of the general population suffer from this disease every year. This causes a huge health, social and economic problem. The reason for such a high incidence of illness is beyond the aging population, poor lifestyle: diet and low physical activity. Diabetes affects people of all ages. Having a disease means a very serious problem for the patient. It essentially changes its life, requires long-term treatment, proper care and lifestyle changes. Aim: Defining the knowledge level of POZ patients on the diagnosis and treatment of type 2 diabetes. Material and method: The study group consisted of patients reporting to the POZ clinic at the Independent Public Health Care Unit in Bychawa. The research group comprised 36 women and 37 men. The research tool was an author's questionnaire, which included a total of 47 questions, 11 of them metric, and the remaining 36 related to knowledge about diabetes. Questions were closed questions. The results of the study were statistically analyzed. The values of the measured measurable parameters are expressed by means of mean, standard deviation, minimum and maximum values, and non-measurable characteristics by means of numerical and interest. Standard deviation is a popular measure of dispersion reflecting the degree of dispersion of measurements around the arithmetic mean. The correlation between variables was used to correlate Sperman (R) rankings. The significance level p <0.05 has been assumed to indicate the existence of statistically significant differences or dependencies. The database and statistical studies were based on Statistica 9.1 computer software. (StatSoft, Poland). Results: The knowledge of patients with type II diabetes mellitus is incomplete and high, and quite often they have knowledge in this field. Most respondents have general knowledge about the treatment and diagnosis of diabetes Conclusions: The knowledge level of people with diabetes is insufficient. Respondents have incomplete knowledge about the diagnosis of type 2 diabetes. There is a connection between knowledge about the diagnosis and treatment of type 2 diabetes and the characteristics of the study population. People with secondary and tertiary education have a higher level of knowledge about recognizing type II diabetes than people with primary and vocational education. Likewise, the results of treatment for diabetes are similar, and higher education holders have more knowledge.